2023
DOI: 10.1007/s00787-023-02140-9
|View full text |Cite
|
Sign up to set email alerts
|

What treatment outcomes matter in adolescent depression? A Q-study of priority profiles among mental health practitioners in the UK and Chile

Abstract: Evidence-based and person-centred care requires the measurement of treatment outcomes that matter to youth and mental health practitioners. Priorities, however, may vary not just between but also within stakeholder groups. This study used Q-methodology to explore differences in outcome priorities among mental health practitioners from two countries in relation to youth depression. Practitioners from the United Kingdom (UK) (n = 27) and Chile (n = 15) sorted 35 outcome descriptions by importance and completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
2
2
0
Order By: Relevance
“…Based on these results, treatment failure or success is not a straightforward matter. These results are consistent with findings of other studies that have similarly reported differences between outcomes recorded through self-report measures and those based on qualitative interviews (McElvaney and Timulak, 2013;Bloch-Elkouby et al, 2019;De Smet et al, 2019, 2020a,b, 2021a,b, 2024Desmet et al, 2021a). Taken together, the evidence from these studies as a whole suggest that the phenomenon that we have characterized as paradoxical outcome is a robust pattern that has been identified in different samples using different data collection and analysis strategies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on these results, treatment failure or success is not a straightforward matter. These results are consistent with findings of other studies that have similarly reported differences between outcomes recorded through self-report measures and those based on qualitative interviews (McElvaney and Timulak, 2013;Bloch-Elkouby et al, 2019;De Smet et al, 2019, 2020a,b, 2021a,b, 2024Desmet et al, 2021a). Taken together, the evidence from these studies as a whole suggest that the phenomenon that we have characterized as paradoxical outcome is a robust pattern that has been identified in different samples using different data collection and analysis strategies.…”
Section: Discussionsupporting
confidence: 91%
“…There are several factors that may contribute to the occurrence of paradoxical outcomes. When evaluating the effectiveness of therapy they have received, clients make reference to a much wider range of criteria than those covered by commonly-used symptom measures ( Chevance et al, 2020 ; Bear et al, 2021 ; Housby et al, 2021 ; Krause et al, 2021 ; Axelsdóttir et al, 2022 ; Morton et al, 2022 ; Amin Choudhury et al, 2023 ; Kohne et al, 2023 ; Krause et al, 2024 ). As a consequence, in a post-therapy interview, a client may judge therapy to be successful or otherwise on the basis of factors that are not measured in an outcome scale.…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors that may contribute to the occurrence of paradoxical outcomes. When evaluating the effectiveness of therapy they have received, clients make reference to a much wider range of criteria than those covered by commonly-used symptom measures (Chevance et al, 2020;Bear et al, 2021;Housby et al, 2021;Krause et al, 2021;Axelsdóttir et al, 2022;Morton et al, 2022;Amin Choudhury et al, 2023;Kohne et al, 2023;Krause et al, 2024). As a consequence, in a post-therapy interview, a client may judge therapy to be successful or otherwise on the basis of factors that are not measured in an outcome scale.…”
Section: Introductionmentioning
confidence: 99%